Inter-rater reliability of Centor score assessments between telemedicine and in-person examinations in patients with an acute sore throat - Patrycja Woldan-Gradalska; Wojciech Gradalski; Sikandar Moradi; Martin Franzelius; Sara Folkerman; Eva-Maria Fuchs; Frida Liljegren; Therese Karlsson; Hálfdán Pétursson; Anette Larsson; Ingmarie Skoglund; Ronny K. Gunnarsson; et al. (Infectious Diseases, 2025)

Assessing tetraether lipids as a paleotemperature proxy on western edge of the Chinese Loess Plateau: A cautionary tale - Jingjing Guo; Louise Fuchs; Martin Ziegler; Youbin Sun; Francien Peterse (Organic Geochemistry, 2025)

Improving an existing proxy-based approach for floodplain denitrification assessment to facilitate decision making on restoration - Ute Susanne Kaden; Christiane Schulz-Zunkel; Elmar Fuchs; Peter Horchler; Hans Dieter Kasperidus; Otavio de Moraes Bonilha; Holger Rupp; Martin Tschikof; Gabriele Weigelhofer; Thomas Hein; Mathias Scholz (Science of The Total Environment, 2023)

A review of standardized high-throughput cardiovascular phenotyping with a link to metabolism in mice - Jiri Lindovsky; Zuzana Nichtova; Nathalia R. V. Dragano; David Pajuelo Reguera; Jan Prochazka; Helmut Fuchs; Susan Marschall; Valerie Gailus-Durner; Radislav Sedlacek; Martin Hrabě de Angelis; Jan Rozman; Nadine Spielmann (Mammalian Genome, 2023)
Cardiovascular diseases cause a high mortality rate worldwide and represent a major burden for health care systems. Experimental rodent models play a central role in cardiovascular disease research by effectively simulating human cardiovascular diseases. Using mice, the International Mouse Phenotyping Consortium (IMPC) aims to target each protein-coding gene and phenotype multiple organ systems in single-gene knockout models by a global network of mouse clinics. In this review, we summarize the current advances of the IMPC in cardiac research and describe in detail the diagnostic requirements of high-throughput electrocardiography and transthoracic echocardiography capable of detecting cardiac arrhythmias and cardiomyopathies in mice. Beyond that, we are linking metabolism to the heart and describing phenotypes that emerge in a set of known genes, when knocked out in mice, such as the leptin receptor ( Lepr ), leptin ( Lep ), and Bardet–Biedl syndrome 5 ( Bbs5 ). Furthermore, we are presenting not yet associated loss-of-function genes affecting both, metabolism and the cardiovascular system, such as the RING finger protein 10 ( Rfn10 ), F-box protein 38 ( Fbxo38 ), and Dipeptidyl peptidase 8 ( Dpp8 ). These extensive high-throughput data from IMPC mice provide a promising opportunity to explore genetics causing metabolic heart disease with an important translational approach.

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Echo2Pheno: a deep-learning application to uncover echocardiographic phenotypes in conscious mice - Christina Bukas; Isabella Galter; Patricia da Silva-Buttkus; Helmut Fuchs; Holger Maier; Valerie Gailus-Durner; Christian L. Müller; Martin Hrabě de Angelis; Marie Piraud; Nadine Spielmann (Mammalian Genome, 2023)
Echocardiography, a rapid and cost-effective imaging technique, assesses cardiac function and structure. Despite its popularity in cardiovascular medicine and clinical research, image-derived phenotypic measurements are manually performed, requiring expert knowledge and training. Notwithstanding great progress in deep-learning applications in small animal echocardiography, the focus has so far only been on images of anesthetized rodents. We present here a new algorithm specifically designed for echocardiograms acquired in conscious mice called Echo2Pheno, an automatic statistical learning workflow for analyzing and interpreting high-throughput non-anesthetized transthoracic murine echocardiographic images in the presence of genetic knockouts. Echo2Pheno comprises a neural network module for echocardiographic image analysis and phenotypic measurements, including a statistical hypothesis-testing framework for assessing phenotypic differences between populations. Using 2159 images of 16 different knockout mouse strains of the German Mouse Clinic, Echo2Pheno accurately confirms known cardiovascular genotype–phenotype relationships (e.g., Dystrophin) and discovers novel genes (e.g., CCR4-NOT transcription complex subunit 6-like, Cnot6l, and synaptotagmin-like protein 4, Sytl4 ), which cause altered cardiovascular phenotypes, as verified by H&E-stained histological images. Echo2Pheno provides an important step toward automatic end-to-end learning for linking echocardiographic readouts to cardiovascular phenotypes of interest in conscious mice. Graphical abstract

Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.

Knockout of the Complex III subunit Uqcrh causes bioenergetic impairment and cardiac contractile dysfunction - Nadine Spielmann; Christina Schenkl; Tímea Komlódi; Patricia da Silva-Buttkus; Estelle Heyne; Jana Rohde; Oana V. Amarie; Birgit Rathkolb; Erich Gnaiger; Torsten Doenst; Helmut Fuchs; Valérie Gailus-Durner; et al. (Mammalian Genome, 2023)
Ubiquinol cytochrome c reductase hinge protein (UQCRH) is required for the electron transfer between cytochrome c 1 and c of the mitochondrial cytochrome bc 1 Complex (CIII). A two-exon deletion in the human UQCRH gene has recently been identified as the cause for a rare familial mitochondrial disorder. Deletion of the corresponding gene in the mouse ( Uqcrh -KO) resulted in striking biochemical and clinical similarities including impairment of CIII, failure to thrive, elevated blood glucose levels, and early death. Here, we set out to test how global ablation of the murine Uqcrh affects cardiac morphology and contractility, and bioenergetics. Hearts from Uqcrh -KO mutant mice appeared macroscopically considerably smaller compared to wildtype littermate controls despite similar geometries as confirmed by transthoracic echocardiography (TTE). Relating TTE-assessed heart to body mass revealed the development of subtle cardiac enlargement, but histopathological analysis showed no excess collagen deposition. Nonetheless, Uqcrh -KO hearts developed pronounced contractile dysfunction. To assess mitochondrial functions, we used the high-resolution respirometer NextGen-O2k allowing measurement of mitochondrial respiratory capacity through the electron transfer system (ETS) simultaneously with the redox state of ETS-reactive coenzyme Q (Q), or production of reactive oxygen species (ROS). Compared to wildtype littermate controls, we found decreased mitochondrial respiratory capacity and more reduced Q in Uqcrh -KO, indicative for an impaired ETS. Yet, mitochondrial ROS production was not generally increased. Taken together, our data suggest that Uqcrh -KO leads to cardiac contractile dysfunction at 9 weeks of age, which is associated with impaired bioenergetics but not with mitochondrial ROS production. Graphical abstract Global ablation of the Uqcrh gene results in functional impairment of CIII associated with metabolic dysfunction and postnatal developmental arrest immediately after weaning from the mother. Uqcrh -KO mice show dramatically elevated blood glucose levels and decreased ability of isolated cardiac mitochondria to consume oxygen (O 2 ). Impaired development (failure to thrive) after weaning manifests as a deficiency in the gain of body mass and growth of internal organ including the heart. The relative heart mass seemingly increases when organ mass calculated from transthoracic echocardiography (TTE) is normalized to body mass. Notably, the heart shows no signs of collagen deposition, yet does develop a contractile dysfunction reflected by a decrease in ejection fraction and fractional shortening.

A rationale for considering heart/brain axis control in neuropsychiatric disease - Lillian Garrett; Dietrich Trümbach; Nadine Spielmann; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Sabine M. Hölter (Mammalian Genome, 2023)
Neuropsychiatric diseases (NPD) represent a significant global disease burden necessitating innovative approaches to pathogenic understanding, biomarker identification and therapeutic strategy. Emerging evidence implicates heart/brain axis malfunction in NPD etiology, particularly via the autonomic nervous system (ANS) and brain central autonomic network (CAN) interaction. This heart/brain inter-relationship harbors potentially novel NPD diagnosis and treatment avenues. Nevertheless, the lack of multidisciplinary clinical approaches as well as a limited appreciation of molecular underpinnings has stymied progress. Large-scale preclinical multi-systemic functional data can therefore provide supplementary insight into CAN and ANS interaction. We here present an overview of the heart/brain axis in NPD and establish a unique rationale for utilizing a preclinical cardiovascular disease risk gene set to glean insights into heart/brain axis control in NPD. With a top-down approach focusing on genes influencing electrocardiogram ANS function, we combined hierarchical clustering of corresponding regional CAN expression data and functional enrichment analysis to reveal known and novel molecular insights into CAN and NPD. Through ‘support vector machine’ inquiries for classification and literature validation, we further pinpointed the top 32 genes highly expressed in CAN brain structures altering both heart rate/heart rate variability (HRV) and behavior. Our observations underscore the potential of HRV/hyperactivity behavior as endophenotypes for multimodal disease biomarker identification to index aberrant executive brain functioning with relevance for NPD. This work heralds the potential of large-scale preclinical functional genetic data for understanding CAN/ANS control and introduces a stepwise design leveraging preclinical data to unearth novel heart/brain axis control genes in NPD.

Development and Evaluation of Options for Action to Progress on the SDG 6 Targets in Austria - Verena Germann; Florian Borgwardt; Jörg Fischer; Daniela Fuchs-Hanusch; Martin Regelsberger; Gerhard Schubert; Annett Uhmann; Günter Langergraber (Journal of Environmental Management, 2023)

Applicability and limitations of high-throughput algal growth rate measurements using in vivo fluorescence in microtiter plates - Martin Albrecht; Samira Khanipour Roshan; Laura Fuchs; Ulf Karsten; Rhena Schumann (Journal of Applied Phycology, 2022)
Micro-algae play important roles in primary production, nutrient cycling, and applied biotechnology. Mico-algae are phylogenetically, morphologically and physiologically diverse and often easy to grow in cultures. Growth is the key parameter of viability and crucial for survival in situ and efficiency in vitro . Therefore, growth is often used in eco-physiological experiments to describe the fundamental niche and optimum conditions. In vivo chlorophyll- a fluorescence (IVCF) is a well-established proxy for the growth of micro-algae and is based on constant cell properties during exponential growth. High-throughput IVCF measurements have been applied for about 20 years for few, mostly green algal strains. Here, we tested the IVCF using microtiter plates on strains of four different algal phyla (Chlorophyceae, Cyanobacteria, Bacillariophyceae, Rhodophyceae) and compared the data with cell counts and chlorophyll contents. The microtiter plate reader based IVCF (MPR-IVCF) approach worked best for the diatom Cylindrotheca closterium and the cyanobacterium Synechococcus elongatus . Differences between IVCF and cell count-based growth rates were found for Chlorella vulgaris and Rhodella sp. The IVCF growth rates were lower than the growth rates based on cell counts in both cases, thus underestimating absolute growth rates. The MPR-IVCF method is robust in terms of light scattering and non-photosynthetic contamination but prone to changes in light regimes and also to aggregating algal cells. Thus, we recommend using the MPR-IVCF approach (1) for diatoms and cyanobacteria as an absolute growth rate measure, (2) for relative measures of growth rates, intra and interspecific during the same experiment, also for all algal phyla except Rhodophyta.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Species-specific breeding habitat association of declining farmland birds within urban environments: conservation implications - Jan Havlíček; Jan Riegert; Jaroslava Bandhauerová; Roman Fuchs; Martin Šálek (Urban Ecosystems, 2021)

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

Tick species from cattle in the Adama Region of Ethiopia and pathogens detected - Tafese Beyene Tufa; Silke Wölfel; Dana Zubriková; Bronislava Víchová; Martin Andersson; Ramona Rieß; Liliana Rutaihwa; André Fuchs; Hans Martin Orth; Dieter Häussinger; Torsten Feldt; Sven Poppert; et al. (Experimental and Applied Acarology, 2021)
Ticks will diminish productivity among farm animals and transmit zoonotic diseases. We conducted a study to identify tick species infesting slaughter bulls from Adama City and to screen them for tick-borne pathogens. In 2016, 291 ticks were collected from 37 bulls in Adama, which were ready for slaughter. Ticks were identified morphologically. Total genomic DNA was extracted from ticks and used to test for Rickettsia spp. with real-time PCR. Species identification was done by phylogenetic analysis using sequencing that targeted the 23S-5S intergenic spacer region and ompA genes. Four tick species from two genera, Amblyomma and Rhipicephalus , were identified. Amblyomma cohaerens was the dominant species (n = 241, 82.8%), followed by Amblyomma variegatum (n = 22, 7.5%), Rhipicephalus pulchellus (n = 19, 6.5%), and Rhipicephalus decoloratus (n = 9, 3.0%). Among all ticks, 32 (11%) were positive for Rickettsia spp. and 15 (5.2%) of these were identified as R. africae comprising at least two genetic clades, occurring in A. variegatum (n = 10) and A. cohaerens (n = 5). The remainder of Rickettsia -positive samples could not be amplified due to low DNA yield. Furthermore, another 15 (5.2%) samples carried other pathogenic bacteria: Ehrlichia ruminantium (n = 9; 3.1%) in A. cohaerens , Ehrlichia sp. (n = 3; 1%) in Rh. pulchellus and A. cohaerens , Anaplasma sp. (n = 1; 0.5%) in A. cohaerens , and Neoehrlichia mikurensis (n = 2; 0.7%) in A. cohaerens. All ticks were negative for Bartonella spp., Babesia spp., Theileria spp., and Hepatozoon spp. We reported for the first time E. ruminatium , N. mikurensis , Ehrlichia sp., and Anaplasma sp. in A. cohaerens. Medically and veterinarily important pathogens were mostly detected from A. variegatum and A. cohaerens. These data are relevant for a One-health approach for monitoring and prevention of tick-borne disease transmission.

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Game characteristics in elite para table tennis - Michael Fuchs; Irene Renate Faber; Martin Lames (German Journal of Exercise and Sport Research, 2019)

Crybb2 Mutations Consistently Affect Schizophrenia Endophenotypes in Mice - Tamara Heermann; Lillian Garrett; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Jochen Graw; Sabine M. Hölter (Molecular Neurobiology, 2019)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Models meet data: Challenges and opportunities in implementing land management in Earth system models - Julia Pongratz; Han Dolman; Axel Don; Karl‐Heinz Erb; Richard Fuchs; Martin Herold; Chris Jones; Tobias Kuemmerle; Sebastiaan Luyssaert; Patrick Meyfroidt; Kim Naudts (Global Change Biology, 2018)
As the applications of Earth system models ( ESM s) move from general climate projections toward questions of mitigation and adaptation, the inclusion of land management practices in these models becomes crucial. We carried out a survey among modeling groups to show an evolution from models able only to deal with land‐cover change to more sophisticated approaches that allow also for the partial integration of land management changes. For the longer term a comprehensive land management representation can be anticipated for all major models. To guide the prioritization of implementation, we evaluate ten land management practices—forestry harvest, tree species selection, grazing and mowing harvest, crop harvest, crop species selection, irrigation, wetland drainage, fertilization, tillage, and fire—for (1) their importance on the Earth system, (2) the possibility of implementing them in state‐of‐the‐art ESM s, and (3) availability of required input data. Matching these criteria, we identify “low‐hanging fruits” for the inclusion in ESM s, such as basic implementations of crop and forestry harvest and fertilization. We also identify research requirements for specific communities to address the remaining land management practices. Data availability severely hampers modeling the most extensive land management practice, grazing and mowing harvest, and is a limiting factor for a comprehensive implementation of most other practices. Inadequate process understanding hampers even a basic assessment of crop species selection and tillage effects. The need for multiple advanced model structures will be the challenge for a comprehensive implementation of most practices but considerable synergy can be gained using the same structures for different practices. A continuous and closer collaboration of the modeling, Earth observation, and land system science communities is thus required to achieve the inclusion of land management in ESM s.

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

A novel biological function of soluble biglycan: Induction of erythropoietin production and polycythemia - Helena Frey; Kristin Moreth; Louise Tzung-Harn Hsieh; Jinyang Zeng-Brouwers; Birgit Rathkolb; Helmut Fuchs; Valérie Gailus-Durner; Renato V. Iozzo; Martin Hrabě de Angelis; Liliana Schaefer (Glycoconjugate Journal, 2017)

Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Arvind Varsani; Philippe Roumagnac; Marc Fuchs; Jesús Navas-Castillo; Enrique Moriones; Ali Idris; Rob W. Briddon; Rafael Rivera-Bustamante; F. Murilo Zerbini; Darren P Martin (Archives of Virology, 2017)

Von den Flitterwochen zur distanzierten Partnerschaft - Martina Fuchs; Martin Schalljo (Standort, 2017)

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

Land management: data availability and process understanding for global change studies - Karl‐Heinz Erb; Sebastiaan Luyssaert; Patrick Meyfroidt; Julia Pongratz; Axel Don; Silvia Kloster; Tobias Kuemmerle; Tamara Fetzel; Richard Fuchs; Martin Herold; Helmut Haberl; Chris D. Jones; et al. (Global Change Biology, 2017)
In the light of daunting global sustainability challenges such as climate change, biodiversity loss and food security, improving our understanding of the complex dynamics of the Earth system is crucial. However, large knowledge gaps related to the effects of land management persist, in particular those human‐induced changes in terrestrial ecosystems that do not result in land‐cover conversions. Here, we review the current state of knowledge of ten common land management activities for their biogeochemical and biophysical impacts, the level of process understanding and data availability. Our review shows that ca. one‐tenth of the ice‐free land surface is under intense human management, half under medium and one‐fifth under extensive management. Based on our review, we cluster these ten management activities into three groups: (i) management activities for which data sets are available, and for which a good knowledge base exists (cropland harvest and irrigation); (ii) management activities for which sufficient knowledge on biogeochemical and biophysical effects exists but robust global data sets are lacking (forest harvest, tree species selection, grazing and mowing harvest, N fertilization); and (iii) land management practices with severe data gaps concomitant with an unsatisfactory level of process understanding (crop species selection, artificial wetland drainage, tillage and fire management and crop residue management, an element of crop harvest). Although we identify multiple impediments to progress, we conclude that the current status of process understanding and data availability is sufficient to advance with incorporating management in, for example, Earth system or dynamic vegetation models in order to provide a systematic assessment of their role in the Earth system. This review contributes to a strategic prioritization of research efforts across multiple disciplines, including land system research, ecological research and Earth system modelling.

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

Assessing the influence of historic net and gross land changes on the carbon fluxes of Europe - Richard Fuchs; Catharina J. E. Schulp; Geerten M. Hengeveld; Peter H. Verburg; Jan G. P. W. Clevers; Mart‐Jan Schelhaas; Martin Herold (Global Change Biology, 2016)
Legacy effects of land cover/use on carbon fluxes require considering both present and past land cover/use change dynamics. To assess past land use dynamics, model‐based reconstructions of historic land cover/use are needed. Most historic reconstructions consider only the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). Studies about the impact of gross and net land change accounting methods on the carbon balance are still lacking. In this study, we assessed historic changes in carbon in soils for five land cover/use types and of carbon in above‐ground biomass of forests. The assessment focused on Europe for the period 1950 to 2010 with decadal time steps at 1‐km spatial resolution using a bookkeeping approach. To assess the implications of gross land change data, we also used net land changes for comparison. Main contributors to carbon sequestration between 1950 and 2010 were afforestation and cropland abandonment leading to 14.6 PgC sequestered carbon (of which 7.6 PgC was in forest biomass). Sequestration was highest for old‐growth forest areas. A sequestration dip was reached during the 1970s due to changes in forest management practices. Main contributors to carbon emissions were deforestation (1.7 PgC) and stable cropland areas on peaty soils (0.8 PgC). In total, net fluxes summed up to 203 TgC yr −1 (98 TgC yr −1 in forest biomass and 105 TgC yr −1 in soils). For areas that were subject to land changes in both reconstructions (35% of total area), the differences in carbon fluxes were about 68%. Overall for Europe the difference between accounting for either gross or net land changes led to 7% difference (up to 11% per decade) in carbon fluxes with systematically higher fluxes for gross land change data.

Exome sequencing identifies a nonsense mutation in Fam46a associated with bone abnormalities in a new mouse model for skeletal dysplasia - Susanne Diener; Sieglinde Bayer; Sibylle Sabrautzki; Thomas Wieland; Birgit Mentrup; Gerhard K. H. Przemeck; Birgit Rathkolb; Elisabeth Graf; Wolfgang Hans; Helmut Fuchs; Marion Horsch; Thomas Schwarzmayr; et al. (Mammalian Genome, 2016)

Single-crystal structure and Raman spectroscopy of synthetic titanite analog CaAlSiO4F - Hannes Krüger; Daniel M. Többens; Peter Tropper; Udo Haefeker; Volker Kahlenberg; Martin R. Fuchs; Vincent Olieric; Ulrike Troitzsch (Mineralogy and Petrology, 2015)

Principles and application of LIMS in mouse clinics - Holger Maier; Christine Schütt; Ralph Steinkamp; Anja Hurt; Elida Schneltzer; Philipp Gormanns; Christoph Lengger; Mark Griffiths; David Melvin; Neha Agrawal; Rafael Alcantara; Arthur Evans; et al. (Mammalian Genome, 2015)

Performance of the COSERO precipitation–runoff model under non-stationary conditions in basins with different climates - Harald Kling; Philipp Stanzel; Martin Fuchs; Hans-Peter Nachtnebel (Hydrological Sciences Journal, 2015)

Screen for alterations of iron related parameters in N-ethyl-N-nitrosourea-treated mice identified mutant lines with increased plasma ferritin levels - Birgit Rathkolb; Martina Klempt; Sibylle Sabrautzki; Dian Michel; Matthias Klaften; Jürgen Laufs; Reinhard Sedlmeier; Wolfgang Hans; Helmut Fuchs; Martina U. Muckenthaler; Marion Horsch; Dean R. Campagna; et al. (BioMetals, 2015)

Gross changes in reconstructions of historic land cover/use for Europe between 1900 and 2010 - Richard Fuchs; Martin Herold; Peter H. Verburg; Jan G.P.W. Clevers; Jonas Eberle (Global Change Biology, 2015)
Historic land‐cover/use change is important for studies on climate change, soil carbon, and biodiversity assessments. Available reconstructions focus on the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). This leads to a serious underestimation of land‐cover/use dynamics with impacts on the biogeochemical and environmental assessments based on these reconstructions. In this study, we quantified to what extent land‐cover/use reconstructions underestimate land‐cover/use changes in Europe for the 1900–2010 period by accounting for net changes only. We empirically analyzed available historic land‐change data, quantified their uncertainty, corrected for spatial‐temporal effects and identified underlying processes causing differences between gross and net changes. Gross changes varied for different land classes (largest for forest and grassland) and led to two to four times the amount of net changes. We applied the empirical results of gross change quantities in a spatially explicit reconstruction of historic land change to reconstruct gross changes for the EU 27 plus Switzerland at 1 km spatial resolution between 1950 and 2010. In addition, the reconstruction was extended back to 1900 to explore the effects of accounting for gross changes on longer time scales. We created a land‐change reconstruction that only accounted for net changes for comparison. Our two model outputs were compared with five commonly used global reconstructions for the same period and area. In our reconstruction, gross changes led in total to a 56% area change (ca. 0.5% yr −1 ) between 1900 and 2010 and cover twice the area of net changes. All global reconstructions used for comparison estimated fewer changes than our gross change reconstruction. Main land‐change processes were cropland/grassland dynamics and afforestation, and also deforestation and urbanization.

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

High-throughput phenotypic assessment of cardiac physiology in four commonly used inbred mouse strains - Kristin Moreth; Ralf Fischer; Helmut Fuchs; Valérie Gailus-Durner; Wolfgang Wurst; Hugo A. Katus; Raffi Bekeredjian; Martin Hrabě de Angelis (Journal of Comparative Physiology B, 2014)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Long-term experiment to study the development, interaction, and influencing factors of DEXA parameters - Helmut Fuchs; Christine Gau; Wolfgang Hans; Valerie Gailus-Durner; Martin Hrabě de Angelis (Mammalian Genome, 2013)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Mathias Schlegel; Lukáš Radosa; Ulrike M. Rosenfeld; Sabrina Schmidt; Cornelia Triebenbacher; Paul-Walter Löhr; Dieter Fuchs; Marta Heroldová; Eva Jánová; Michal Stanko; Ladislav Mošanský; Jana Fričová; et al. (Virus Genes, 2012)

Das Wasserkraftpotenzial Österreichs im Spannungsfeld von Umweltpolitik und Klimawandel - Martin Fuchs; Ernst Zeller; Anne Joeppen; Herbert Weilguni; Harald Kling (WASSERWIRTSCHAFT, 2012)

GOCE gravitational gradients along the orbit - Johannes Bouman; Sophie Fiorot; Martin Fuchs; Thomas Gruber; Ernst Schrama; Christian Tscherning; Martin Veicherts; Pieter Visser (Journal of Geodesy, 2011)

Strategische Umweltprüfung für den Ausbau der Kleinwasserkraft im Einzugsgebiet des Aragvi - Martin Fuchs; Herbert Weilguni; Martin Lagler; Richard Temsch; Bernhard Pelikan (WASSERWIRTSCHAFT, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Pflanzen neu entdecken: Rheinauer Thesen zu Rechten von Pflanzen - Florianne Koechlin; Daniel Ammann; Eva Gelinsky; Benny Haerlin; Martin Ott; Beat Sitter-Liver; Werner Stumpf; Edgar Wagner; Amadeus Zschunke; Günter Altner; Nikolai Fuchs; A. Heistinger; et al. (Journal of Consumer Protection and Food Safety, 2009)

Abundance, distribution, and territory areas of rock-dwelling Lake Tanganyika cichlid fish species - Christian Sturmbauer; Corinna Fuchs; Georg Harb; Elisabeth Damm; Nina Duftner; Michaela Maderbacher; Martin Koch; Stephan Koblmüller (Hydrobiologia, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Power matters in closing the phenotyping gap - Carola W. Meyer; Ralf Elvert; André Scherag; Nicole Ehrhardt; Valerie Gailus-Durner; Helmut Fuchs; Helmut Schäfer; Martin Hrabé de Angelis; Gerhard Heldmaier; Martin Klingenspor (The Science of Nature, 2007)

Morphologic and molecular characterization of two novel Krt71 (Krt2-6g) mutations: Krt71 rco12 and Krt71 rco13 - Fabian Runkel; Matthias Klaften; Kerstin Koch; Volker Böhnert; Heinrich Büssow; Helmut Fuchs; Thomas Franz; Martin Hrabé de Angelis (Mammalian Genome, 2006)

New ENU-induced semidominant mutation, Ali18, causes inflammatory arthritis, dermatitis, and osteoporosis in the mouse - Koichiro Abe; Helmut Fuchs; Thomas Lisse; Wolfgang Hans; Martin Hrabé de Angelis (Mammalian Genome, 2006)

Genotype-specific environmental impact on the variance of blood values in inbred and F1 hybrid mice - Martina Klempt; Birgit Rathkolb; Edith Fuchs; Martin Hrabé de Angelis; Eckhard Wolf; Bernhard Aigner (Mammalian Genome, 2006)

A Myo7a mutation cosegregates with stereocilia defects and low-frequency hearing impairment - Charlotte R. Rhodes; Ronna Hertzano; Helmut Fuchs; Rachel E. Bell; Martin Hrabé de Angelis; Karen P. Steel; Karen B. Avraham (Mammalian Genome, 2004)

An ENU-induced mutation in AP-2α leads to middle earand ocular defects in Doarad mice - Nadav Ahituv; Alexandra Erven; Helmut Fuchs; Keren Guy; Ruth Ashery–Padan; Trevor Williams; Martin Hrabe de Angelis; Karen B. Avraham; Karen P. Steel (Mammalian Genome, 2004)

V76D mutation in a conserved gD-crystallin region leads to dominant cataracts in mice - Jochen Graw; Jana Löster; Dian Soewarto; Helmut Fuchs; André Reis; Eckhard Wolf; Rudi Balling; Martin Angelis (Mammalian Genome, 2002)

MouseNet© database: digital management of a large-scale mutagenesis project - Walter Pargent; Stephan Heffner; Karlheinz F. Schäble; Dian Soewarto; Helmut Fuchs; Martin Hrabé de Angelis (Mammalian Genome, 2000)

The clinical-chemical screen in the Munich ENU Mouse Mutagenesis Project: screening for clinically relevant phenotypes - Birgit Rathkolb; Tanja Decker; Edith Fuchs; Dian Soewarto; Christiane Fella; Stephan Heffner; Walter Pargent; Rüdiger Wanke; Rudi Balling; Martin Hrabé de Angelis; Helmut J. Kolb; Eckhard Wolf (Mammalian Genome, 2000)

Screening for dysmorphological abnormalities—a powerful tool to isolate new mouse mutants - Helmut Fuchs; Klaus Schughart; Eckhard Wolf; Rudi Balling; Martin Hrabé de Angelis (Mammalian Genome, 2000)

Molecular Mechanisms of Bacterial Pathogenicity - Thilo Martin Fuchs (The Science of Nature, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)